Isolation and Molecular Characterization of Corynebacterium pseudotuberculosis: Association with Proinflammatory Cytokines in Caseous Lymphadenitis Pyogranulomas - Helmy A. Torky; Hebatallah M. Saad; Samy A. Khaliel; Asmaa T. Kassih; Jean-Marc Sabatier; Gaber El-Saber Batiha; Helal F. Hetta; Eman M. Elghazaly; Michel De Waard (Animals, 2023)
Corynebacterium pseudotuberculosis (C. pseudotuberculosis) is a causative agent of numerous chronic diseases, including caseous lymphadenitis (CLA) in sheep and goats, which has a zoonotic potential in humans in addition to a poor therapeutic response. In this study, out of 120 collected samples, only 12 (10%) were positive for C. pseudotuberculosis by PCR and by intraperitoneal injection of male Guinea pigs and then characterized for antimicrobial susceptibility and its genetic-relatedness by enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR), which showed 2–4 bands ranging from 100 to 3000 bp that can be clustered into four clusters (C1–C4). Despite the serotype biovar 1 only infecting sheep and goats, ERIC–PCR reveals intra-subtyping variation. Examination of affected LNs and organs revealed marked enlargement with either thick creamy green pus or multiple abscesses of variable sizes with a central caseated core surrounded by dense fibrous capsule. A histopathological examination revealed a central necrotic core surrounded by a peripheral mantle of mononuclear cells and a fibrous capsule. Positive immune expression of nuclear factor kappa B (NF-κB/p65) and interleukin-1β (IL-1β) and negative expression of tumor necrosis factor (TNF) in CLA is the first report to our knowledge. Conclusion: In CLA pyogranulomas, IL1β is a more crucial proinflammatory cytokine than TNF in the regulation of C. pseudotuberculosis infection, which is accompanied by marked NF-κB immunoexpression. Therefore, the NF-κB/p65 signaling pathway is involved in the activation of IL1β, and additional immunohistochemical studies are required to determine the various roles of NF-κB/p65 in the inflammatory response within CLA pyogranulomas to control this pathogen.